Dual role of autophagy in hallmarks of cancer - Singh, Shikha Satendra; Vats, Somya; Chia, Amelia Yi-Qian; Tan, Tuan Zea; Deng, Shuo; Ong, Mei Shan; Arfuso, Frank; Yap, Celestial T.; Goh, Boon Cher; Sethi, Gautam; Huang, Ruby Yun-Ju; Shen, Han Ming; et al. (Oncogene, 2018)
Evolutionarily conserved across eukaryotic cells, macroautophagy (herein autophagy) is an intracellular catabolic degradative process targeting damaged and superfluous cellular proteins, organelles, and other cytoplasmic components. Mechanistically, it involves formation of double-membrane vesicles called autophagosomes that capture cytosolic cargo and deliver it to lysosomes, wherein the breakdown products are eventually recycled back to the cytoplasm. Dysregulation of autophagy often results in various disease manifestations, including neurodegeneration, microbial infections, and cancer. In the case of cancer, extensive attention has been devoted to understanding the paradoxical roles of autophagy in tumor suppression and tumor promotion. In this review, while we summarize how this self-eating process is implicated at various stages of tumorigenesis, most importantly, we address the link between autophagy and hallmarks of cancer. This would eventually provide a better understanding of tumor dependence on autophagy. We also discuss how therapeutics targeting autophagy can counter various transformations involved in tumorigenesis. Finally, this review will provide a novel insight into the mutational landscapes of autophagy-related genes in several human cancers, using genetic information collected from an array of cancers.